2007
DOI: 10.1038/oby.2007.518
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acid Pattern in Liver and Erythrocyte Phospholipids from Obese Patients

Abstract: ELIZONDO, ALEJANDRA, JULIA ARAYA, RAMÓ N RODRIGO, JAIME PONIACHIK, ATTILA CSENDES, FERNANDO MALUENDA, JUAN C. DÍAZ, CINZIA SIGNORINI, CRISTIANA SGHERRI, MARIO COMPORTI, AND LUIS A. VIDELA. Polyunsaturated fatty acid pattern in liver and erythrocyte phospholipids from obese patients Obesity. 2007;15:24 -31. Objective: Our aim was to study the fatty acid (FA) composition of liver phospholipids and its relation to that in erythrocyte membranes from patients with obese nonalcoholic fatty liver disease (NAFLD), as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
95
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(104 citation statements)
references
References 36 publications
6
95
0
2
Order By: Relevance
“…Epidemiologic studies report that an intake of fish [7] and n-3 PUFAs [8,32] as well as an erythrocyte level of n-3 PUFA [12,33] were negatively associated with the risk of NAFLD. Our previous study showed that hepatic content of triglycerides was decreased by the downregulation of hepatic triglyceride synthesis and the upregulation of hepatic triglyceride oxidation in rats fed n-3 PUFA [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiologic studies report that an intake of fish [7] and n-3 PUFAs [8,32] as well as an erythrocyte level of n-3 PUFA [12,33] were negatively associated with the risk of NAFLD. Our previous study showed that hepatic content of triglycerides was decreased by the downregulation of hepatic triglyceride synthesis and the upregulation of hepatic triglyceride oxidation in rats fed n-3 PUFA [34].…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies also report that the risk of NAFLD is positively associated with an intake of saturated fatty acids [8], fructose from beverages [9], refined grain, red meat, and processed meat [10] and negatively associated with an intake of vegetables [11] and fish rich in n-3 polyunsaturated fatty acids (PUFAs) [7]. In addition, Elizondo et al [12] showed that the erythrocyte level of n-3 PUFA, a marker for fish intake, was significantly lower in patients with NAFLD than healthy controls. Recent meta-analysis of randomized controlled trials consistently reported that n-3 PUFA supplementation could be a practical and effective treatment for NAFLD [13,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NAFLD consume less n-3 PUFAs than controls [38,39.] A systematic review and meta-analysis showed that supplementation with n-3 PUFA decreases liver fat but does not have a statistically significant effect on ALT levels [40].…”
Section: Dietmentioning
confidence: 99%
“…In detail, we have found that a combination of high palmitoleic acid (C16:1), low polyunsaturated fatty acids (PUFA) (especially omega 6) and high endogenous trans fatty acids (TFA), that reflect a radical stress activity, are associated with longevity [6]. Elizondo et al demonstrated a correlation between liver and erythrocyte phospholipids PUFA from patients with obese non-alcoholic fatty liver disease and proposed the fatty acid in erythrocytes membranes as reliable biomarker of derangements in liver lipid metabolism in obese patients [7]. Petrescu et al comparing the uptake kinetics of 9,10-[3H] oleic acid by omental adipocytes isolated from obese and non-obese patients undergoing laparoscopic procedures, observed that in the obese subjects long-chain fatty acid (LCFA) uptake was up-regulated, suggesting that alterations in LCFA partitioning may contribute to the obese phenotype [8].…”
Section: Introductionmentioning
confidence: 99%